2017
DOI: 10.1155/2017/3540320
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical and Reaction Behavior of PTFE/Al/Fe2O3 under Impact and Quasi-Static Compression

Abstract: Quasi-static compression and drop-weight test were used to characterize the mechanical and reaction behavior of PTFE/Al/Fe 2 O 3 composites. Two kinds of PTFE/Al/Fe 2 O 3 composites were prepared with different mass of PTFE, and the reaction phenomenon and stress-strain curves were recorded; the residuals after reaction were analyzed by X-ray diffraction (XRD). The results showed that, under quasi-static compression condition, the strength of the materials is increased (from 37.1 Mpa to 77.2 Mpa) with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Madusanka et al synthesized thick film gas sensor using PTFE and α-Fe 2 O 3 nanoparticles [ 16 ] while Kang et al fabricated porous Fe 2 O 3 -PTFE nanofiber membranes for photocatalysis applications [ 17 ]. Moreover, PTFE-Al-Fe 2 O 3 composites were prepared to be used as reactive materials [ 18 ]. The electro-Fenton system was synthesized by combining multiwall carbon nanotubes and Fe@Fe 2 O 3 nanowires with PTFE [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Madusanka et al synthesized thick film gas sensor using PTFE and α-Fe 2 O 3 nanoparticles [ 16 ] while Kang et al fabricated porous Fe 2 O 3 -PTFE nanofiber membranes for photocatalysis applications [ 17 ]. Moreover, PTFE-Al-Fe 2 O 3 composites were prepared to be used as reactive materials [ 18 ]. The electro-Fenton system was synthesized by combining multiwall carbon nanotubes and Fe@Fe 2 O 3 nanowires with PTFE [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years, the main research based on Al/PTFE reaction materials is as follows: (1) study on the composition ratio and mixing methods of Al/PTFE-based active materials; (2) study on the mechanical properties, reaction characteristics, impact sensitivity, ignition mechanism and hot spot formation mechanism of crack tip of Al/PTFE-based active materials; (3) study on the energy release characteristics of Al/PTFE-based active materials; (4) study on the establishment of a theoretical model of impact-induced chemical reaction of Al/PTFE-based active materials. Among them, some scholars introduce high density metals such as Ni [ 13 ], W [ 14 , 15 ] and Ta [ 16 ] into Al/PTFE-based active materials to improve their hardness, density, strength and other characteristics; some scholars have added metal oxides CuO [ 17 ], Fe 2 O 3 [ 18 ] and MnO 2 [ 19 ] to Al/PTFE-based active materials to improve their reaction characteristics; some scholars have added high-energy additives such as TiH 2 [ 20 ] and ZrH 2 [ 21 ] to Al/PTFE-based active materials to improve their energy release characteristics. Based on published literature of the above studies, it can be found that most scholars mainly study the influence of distribution ratio, particle size and other factors on material properties through a given sintering control curve, while few scholars study the influence of sintering control factors on material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 9 studied PTFE/Al/CuO prepared from nano-Al and nano-CuO, and found that PTFE is both an oxidizing agent and a reducing agent, and excess Al also reacts with CuO and releases a large amount of heat. Huang et al 10 studied the mechanical properties of PTFE/Al/Fe 2 O 3 composites. It is found that as the content of PTFE increases, the strength of the material increases and only materials with high PTFE content will react.…”
Section: Introductionmentioning
confidence: 99%